Mimotopes of heat shock proteins of Salmonella enterica serovar Typhi identified from phage-displayed peptide library - Yuen Hawk Leong,1 Shamala Devi,2 Thong Kwai Lin2* (The Journal of Infection in Developing Countries, 2008)
Background: Heat shock proteins (HSPs) are known to be involved in the pathogenesis of Salmonella enterica serovar Typhi (S. Typhi), the causative agent of typhoid fever. The objective of this study was to apply a phage display library to identify mimotopes of two HSPs, HSP90 and DnaK in S. Typhi.Methodology: A 12-mer random peptide library expressed on the surface of the filamentous phage, M13, was used to select the mimotopes of two S. Typhi heat shock proteins by biopanning with monoclonal antibodies (mAbs), DnaK and HSP90. The immunogenicity of the selected peptides was determined through binding affinity with polyclonal antibodies from pooled typhoid-confirmed patients' sera and purified HSPs mAb using Western blotting and ELISA.Results: Five rounds of biopanning resulted in enrichment of phage clones expressing the binding motifs TDxSTRP and FPSHYWLYPPPT, respectively. The selected peptides showed strong immunoreactivity with patients' sera. Thus, monoclonal antibodies against HSP and patient sera can select common mimotopes from the random peptide library.Conclusion: These findings may provide fundamental information for further studies on diagnostic application or vaccine design against this aetiologic agent of typhoid fever.